USE OF CHOREOGRAPHY ELEMENTS IN THE TRAINING PROCESS OF NOVICE ATHLETES FOR THE SUCCESSFUL DEVELOPMENT OF RHYTHMIC GYMNASTICS PROGRAMS - Olga Riabchenko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: apply choreographic training in the training process of novice athletes and determine its influence on the performance of basic rhythmic gymnastics exercises. Material and methods: the pedagogical experiment was carried out on the basis of the Complex Children's Sports School No. 1, Kyivskyi District (Kharkov) among novice athletes 5-6 years old. The study involved 24 gymnasts: the control group (n=12) conducted the training process according to the school program, experimental (n=12) with the additional use of choreographic training. To evaluate the artistic and technical components, 2 choreographers with judicial experience and 4 trainers of the national category were involved. Because the level of preparedness of young athletes was at the initial stage, a 5-point assessment scale was applied. The first assessment of the basic exercises in rhythmic gymnastics among young athletes was carried out in the study groups at the beginning of the school year, the second - at the end of the half-year. Results: in the process of using choreographic exercises for mastering programs in rhythmic gymnastics for novice athletes 5-6 years old from the experimental group, reliably better assessment results were obtained in relation to the control group in performing the following components: "expressiveness of body movement" (t=4,97; p<0,001), "balance" (t=4,48; p<0,001), "character" (t=3,71; p<0,01), "rhythm" (t=4,18; p<0,01), "jumping" (t=3,22; p<0,01) and "turns" (t=3,77; p<0,01). Conclusions: as a result of the research, it was found that the additional use of choreography in the training process of novice athletes of 5-6 years old effectively affects the performance of basic exercises in rhythmic gymnastics, which indicates the successful development of programs in this sport. It is during these classes that posture is formed, the musculoskeletal system is strengthened and the culture of movements of the gymnasts is formed.